2012
DOI: 10.1186/ar3873
|View full text |Cite
|
Sign up to set email alerts
|

C5a and its receptors in human anti-neutrophil cytoplasmic antibody (ANCA)-associated vasculitis

Abstract: IntroductionThe complement system is crucial for the development of antineutrophil cytoplasmic antibody (ANCA)-associated vasculitis (AAV). In particular, C5a plays a central role. In this study, plasma and urinary levels of C5a as well as renal C5a receptors (CD88 and C5L2) expression were investigated in patients with AAV.MethodsTwenty-four patients with AAV in the active phase, 19 patients with AAV in the remission phase, and 20 patients with lupus nephritis (LN) were included. Plasma and urinary levels of … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

3
64
1
3

Year Published

2013
2013
2022
2022

Publication Types

Select...
6
1

Relationship

2
5

Authors

Journals

citations
Cited by 90 publications
(71 citation statements)
references
References 38 publications
3
64
1
3
Order By: Relevance
“…Recently, increasing evidences have suggested an important role of complement activation in the pathogenesis of AAV (6)(7)(8)(9)(10)(11)(12)(13). In the animal study by Xiao et al (7), it was found that activation of the alternative complement pathway, but not the classic or lectin pathway, was required for induction of GN with anti-MPO IgG.…”
Section: Introductionmentioning
confidence: 98%
“…Recently, increasing evidences have suggested an important role of complement activation in the pathogenesis of AAV (6)(7)(8)(9)(10)(11)(12)(13). In the animal study by Xiao et al (7), it was found that activation of the alternative complement pathway, but not the classic or lectin pathway, was required for induction of GN with anti-MPO IgG.…”
Section: Introductionmentioning
confidence: 98%
“…Recent mouse studies have added support to the hypothesis that M1-type, clodronate-sensitive macrophages do participate in initial injury, 11,16 but have also revealed that macrophages are critical for the normal repair processes that inhibit the progression of fibrosis and CKD. [10][11][12] Using several sophisticated mouse models, Lin et al demonstrated that macrophages responding to renal injury produce and release the Wnt ligand Wnt7b that acts on injured and regenerating TECs to promote their continuation through the cell cycle and regeneration of the tubule basement membrane, thus re-establishing renal function and reducing fibrosis. 12 Importantly, it was demonstrated that the M1 macrophages that traffic to the postischemic kidney change their phenotype in situ to the anti-inflammatory M2 phenotype.…”
Section: Nonementioning
confidence: 99%
“…[10][11][12] Using several sophisticated mouse models, Lin et al demonstrated that macrophages responding to renal injury produce and release the Wnt ligand Wnt7b that acts on injured and regenerating TECs to promote their continuation through the cell cycle and regeneration of the tubule basement membrane, thus re-establishing renal function and reducing fibrosis. 12 Importantly, it was demonstrated that the M1 macrophages that traffic to the postischemic kidney change their phenotype in situ to the anti-inflammatory M2 phenotype. 11 Collectively, these studies have greatly enhanced our understanding of the role of macrophages in the normal and abnormal injury and reparative response of the kidney after AKI.…”
Section: Nonementioning
confidence: 99%
See 2 more Smart Citations